Management of Mycobacterium avium complex and Mycobacterium abscessus pulmonary disease: therapeutic advances and emerging treatments. (9th February 2022) - Kumar, Kartik; Daley, Charles L.; Griffith, David E.; Loebinger, Michael R.
Nontuberculous mycobacterial pulmonary disease (NTM-PD) remains a challenging condition to diagnose and treat effectively. Treatment of NTM-PD is prolonged, frequently associated with adverse effects and has variable success. In this review, we consider the factors influencing clinicians when treating NTM-PD and discuss outcomes from key studies on the pharmacological management of Mycobacterium avium complex pulmonary disease and M. abscessus pulmonary disease. We highlight issues relating to treatment-related toxicity and provide an overview of repurposed and emerging therapies for NTM-PD. Despite advances in treatment regimens for nontuberculous mycobacterial pulmonary disease, significant challenges remain. Repurposed and emerging therapies may hold promise. https://bit.ly/3IBPh9q